Possibilities of influencing the crystallization process of bisphenol A- and bisphenol F-based epoxy resins used for hydrophobic coatings on concrete - Seidlová, Michaela; Hodul, Jakub; Žižková, Nikol; Borg, Ruben Paul (MDPI, 2023)
Crystallization of bisphenol A (DGEBA)- and bisphenol F (DGEBF)-based epoxy resins is a natural property of these oligomers. However, manufacturers of coatings and other systems based on these epoxy resins are making efforts to slow down the crystallization process as much as possible, thereby extending the shelf life and improving the competitiveness of their products. This paper focuses on the kinetics of the crystallization process of epoxy resins and the effect of the presence of a certain degree of crystallinity on selected parameters of epoxy-based materials. Furthermore, an analysis of the impact of a certain degree of crystallinity of the epoxy base on the resulting coating parameters was carried out. The highest value of crystallinity (17%) was achieved in the sample containing the highest proportion of DGEBF in the crystallization phase “c”, and the enthalpy of melting (Ht) of the crystalline DGEBF sample was 6.3 J/g. Mechanical parameters as well as chemical and thermal resistance of hydrophobic epoxy systems were investigated. The best abrasion resistance (1.5 cm3/50 cm2) was achieved with the blend containing only amorphous DGEBA. The adhesion of the epoxy samples on concrete was greater than 6.5 MPa. The chemical resistance tests performed showed that, in general, the chemical resistance of epoxy systems decreases with increasing crystallinity content. The tighter arrangement of molecules in the crystalline regions of the epoxy matrix results in an increase in density, strength and hardness. This study presents a comprehensive examination of the crystallization of DGEBA and DGEBF, which is, as yet virtually unavailable. It also contributes to knowledge by outlining the possibility of speeding up or slowing down the crystallization process of epoxy resins, including the principle of selecting nucleating agents.

Crystallization of bisphenol A (DGEBA)- and bisphenol F (DGEBF)-based epoxy resins is a natural property of these oligomers. However, manufacturers of coatings and other systems based on these epoxy resins are making efforts to slow down the crystallization process as much as possible, thereby extending the shelf life and improving the competitiveness of their products. This paper focuses on the kinetics of the crystallization process of epoxy resins and the effect of the presence of a certain degree of crystallinity on selected parameters of epoxy-based materials. Furthermore, an analysis of the impact of a certain degree of crystallinity of the epoxy base on the resulting coating parameters was carried out. The highest value of crystallinity (17%) was achieved in the sample containing the highest proportion of DGEBF in the crystallization phase “c”, and the enthalpy of melting (Ht) of the crystalline DGEBF sample was 6.3 J/g. Mechanical parameters as well as chemical and thermal resistance of hydrophobic epoxy systems were investigated. The best abrasion resistance (1.5 cm3/50 cm2) was achieved with the blend containing only amorphous DGEBA. The adhesion of the epoxy samples on concrete was greater than 6.5 MPa. The chemical resistance tests performed showed that, in general, the chemical resistance of epoxy systems decreases with increasing crystallinity content. The tighter arrangement of molecules in the crystalline regions of the epoxy matrix results in an increase in density, strength and hardness. This study presents a comprehensive examination of the crystallization of DGEBA and DGEBF, which is, as yet virtually unavailable. It also contributes to knowledge by outlining the possibility of speeding up or slowing down the crystallization process of epoxy resins, including the principle of selecting nucleating agents.
Possibilities of influencing the crystallization process of bisphenol A- and bisphenol F-based epoxy resins used for hydrophobic coatings on concrete
Keywords: epoxy resin; crystallization; coatings; mechanical parameters; glass transition temperature; bisphenol; chemical resistance; epoxy resin; crystallization; coatings; mechanical parameters; glass transition temperature; bisphenol; chemical resistance